2022
DOI: 10.1186/s12962-022-00342-7
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the evidence sources applied to cost-effectiveness analyses for older women with primary breast cancer

Abstract: Objective To appraise the sources of evidence and methods to estimate input parameter values in decision-analytic model-based cost-effectiveness analyses of treatments for primary breast cancer (PBC) in older patients (≥ 70 years old). Methods Two electronic databases (Ovid Medline, Ovid EMBASE) were searched (inception until 5 September-2021) to identify model-based full economic evaluations of treatments for older women with PBC as part of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
(184 reference statements)
0
1
0
Order By: Relevance
“…In 2022, a systematic review identified seven economic evaluations of breast cancer treatments for older women [ 11 ]. Most studies in this review ( n = 6; 86%) sourced health utility data from patients younger than 70 years, and adjusted these estimates to correspond with an older population.…”
Section: Introductionmentioning
confidence: 99%
“…In 2022, a systematic review identified seven economic evaluations of breast cancer treatments for older women [ 11 ]. Most studies in this review ( n = 6; 86%) sourced health utility data from patients younger than 70 years, and adjusted these estimates to correspond with an older population.…”
Section: Introductionmentioning
confidence: 99%